Cyphostemma mendesii (Vitaceae), a new species from Angola - de Sousa, F.; Figueiredo, E.; Smith, G. F. (Phytotaxa, 2013)
A new species of Cyphostemma (Vitaceae) is here described: C. mendesii, a succulent geophyte from the Namibe region in southern Angola.